Impact of FDI on economic development: A causality analysis for Singapore ; 1976 - 2002 - Mete Feridun; Yaya Sissoko (International Journal of Economic Sciences and Applied Research, 2011)
This study examines the relationship between economic growth as measured by GDP per capita and foreign direct investment for Singapore, using the methodology of Granger causality and vector auto regression (VAR). Evidence shows that there is a unidirectional Granger causation from foreign direct investment to economic growth.
Keywords: C22; F21; O47; 330; Granger causality; vector auto regression; economic growth